PENINGKATAN HASIL BELAJAR PESERTA DIDIK TENTANG SISTEM PENCERNAAN MANUSIA MELALUI MODEL PROJECT BASED LEARNING DI KELAS V UPTD SDI NUNBAUN DELHA - Padji Kana, Rani J.; Koroh, Taty R.; Nawa, Netty E A (Universitas Nusa Cendana, 2024)
The research aims to improve student learning outcomes about the human digestive system in class V UPTD SDI Nunbaun Delha through the Project Based Learning (PjBL) model. The method used is Classroom Action Research (PTK) which consists of 4 stages, namely planning, implementation, observation, and reflection. Data collection techniques are carried out through observing teacher and student activities as well as testing student learning outcomes. Data collection techniques include observing student and teacher activities and testing student learning outcomes. The research results show that implementing PjBL can improve student learning outcomes. In cycle, I, student and teacher activity reached an average of 71.70% and 72% respectively. In cycle II, student activity increased to 87.15% and teacher activity reached 93%. The learning outcomes test showed a significant increase, in cycle I after implementing the PjBL learning model, out of 18 students there were 5 students, or 27.77% of students who reached the KKTP standard, namely 70 with a score range of 70-100. In cycle II, this happened an increase in which of the 18 students who took the learning outcomes test, as many as 17 students, or 94.44% managed to achieve a score between 70-100 and were declared complete, while 1 student, or 5.55% got a score between 50-69 and was declared not complete. So, it can be concluded that implementing the PjBL learning model can improve student learning outcomes.